Enabling Sub-Terahertz Broadband MIMO Communications With Leaky-Wave Antenna Arrays - Albert Diez-Comas; Duschia M. Bodet; Josep M. Jornet (IEEE Open Journal of the Communications Society)
The increasing demand for high-speed wireless communications has led to the exploration of the terahertz (THz) band, where the broad available bandwidths promise significant data-rate improvements. However, propagation losses and the primarily line-of-sight (LoS) nature of THz channels present challenges for implementing spatial multiplexing in multiple-input multiple-output (MIMO) systems. In this paper, we propose a tilted leaky-wave antenna (LWA) array architecture to enable spatial multiplexing by leveraging the frequency-dependent beam-steering capabilities of LWAs. We present the first experimental implementation of a sub-THz, 2-element tilted LWA array. Our experimental results demonstrate that distinct data streams can be transmitted simultaneously with minimal interference. We also provide an analysis of the achievable data rates as a function of number of antennas and tilting angle, showing significant improvements under specific conditions. We further investigate the potential of a staircase LWA array in a multiuser scenario, showing that LWAs could be deployed in access points (APs) to exploit spatial multiplexing. In addition, we present a capacity comparison of different antenna array technologies. These findings establish the potential of tilted LWA arrays for future (sub-)THz MIMO systems, offering a practical approach to overcome the limitations of conventional spatial multiplexing techniques.